2020
DOI: 10.22551/2020.26.0701.10164
|View full text |Cite
|
Sign up to set email alerts
|

Bi-level erector spinae plane catheters for multiple rib fractures in a high-risk patient

Abstract: Rib fractures are associated with significant morbidity and mortality. Most of the morbidity stems from poorly controlled pain and therefore immobility and weak respiratory effort. Moreover, the number of injured ribs correlates with increasing risk of associated morbidity and mortality. We describe the analgesic management of an elderly co-morbid patient on oral anticoagulant therapy presenting with extensive multilevel rib fractures. According to the Western Trauma Association 2017 risk stratification, her m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Screening of abstracts resulted in 77 papers, following which 40 studies were excluded due to incorrect block or injury, surgical fixation, or for being presented in a conference abstract format. Of the 37 studies included, 10 were case reports, [18][19][20][21][22][23][24][25][26][27] 12 were case series, [28][29][30][31][32][33][34][35][36][37][38][39] 5 were cohort studies, 7,40-43 2 were randomized controlled trials (RCT), 44,45 1 was a prospective interventional study, 46 and 7 were letters to the editor. [47][48][49][50][51][52][53] The majority of studies were published after 2020, with 29% being published in 2022.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening of abstracts resulted in 77 papers, following which 40 studies were excluded due to incorrect block or injury, surgical fixation, or for being presented in a conference abstract format. Of the 37 studies included, 10 were case reports, [18][19][20][21][22][23][24][25][26][27] 12 were case series, [28][29][30][31][32][33][34][35][36][37][38][39] 5 were cohort studies, 7,40-43 2 were randomized controlled trials (RCT), 44,45 1 was a prospective interventional study, 46 and 7 were letters to the editor. [47][48][49][50][51][52][53] The majority of studies were published after 2020, with 29% being published in 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight studies reported objective changes in pain score post administration of ESB using various scoring scales including Numerical Rating Scale (NRS), Visual Analogue Scale (VAS), Defence and Veteran Pain (DVP) score, and a 4 point verbal score. 7,[18][19][20][21][22][23][24][25][27][28][29][30][31]33,34,[36][37][38][39]42,[44][45][46][47][48][49]53 Due to the heterogeneity of scales and time points used to evaluate pain, an average weighted percentage change in pain scores was calculated. The mean reduction in pain scores from pre-block baseline was approximately 40% within the first 24 hours.…”
Section: Pain Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Today, most clinicians utilize the ESP block for unilateral rib fractures, citing "wide coverage" of chest wall analgesia while avoiding the pitfalls of neuraxial anesthesia. 10,11 Indeed, dye studies in cadavers suggest that while both the ESP and retrolaminar blocks achieve epidural and neural foraminal spread, the ESP block also reaches the intercostal nerves. 12 Nevertheless, the clinical utility of a retrolaminar block for rib fractures should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%